Gingival margin elevation in severely damaged teeth: with 18-month follow-up case report - Casco Silva , Diego Fernando (2026)
Gingival margin elevation (GME) is a conservative procedure that relocating the subgingival margin to a more supragingival position using restorative materials. This report describes a clinical case in which a 1 mm flapless crown lengthening was performed, followed by GME with Filtek Supreme Flowable Restorative resin (3M ESPE, St. Paul, MN, USA) and Filtek Z350 XT composite resin (3M ESPE, St. Paul, MN, USA) as a pre-endodontic restoration. Subsequently; endodontic retreatments were completed and indirect partial coverage (onlays) were adhesive cemented on the structurally compromised lower right first and second molars. The case demostrates  the clinical viability of GME in two multirooted teeth, with functional and aesthetic results satisfactorily maintained over an 18-month follow-up.